Prevalence of intestinal parasitic infections among patients attending in a tertiary care hospital of eastern region of Nepal – A retrospective, laboratory based study - Baral, Ratna; Jha, Pramod; Amatya, Ritu; Khanal, Basudha (Asian Journal of Medical Sciences, 2017)
Background: Intestinal parasitosis still constitutes one of the major causes of public health problems in the world, particularly in developing countries. Nepal is a small, impoverished country prevalent to infectious diseases, including intestinal parasitosis. Poverty, lack of awareness, failure to practice proper hand washing after defecation, practice of open defecation, unsafe drinking water and use of improper toilets are some of the reasons causing of parasitic infections. Aims and Objective: To determine the types of intestinal parasites in stool samples of patients attending to hospital. Materials and Methods: Stools specimens collected in standard stool vial were submitted in microbiology (2006-2010) unit at BP Koirala Institute of Health Sciences hospital (BPKIHS) were examined for intestinal parasites by direct wet mount using normal saline (0.9%) and lugol’s iodine (0.5%). Results: A total of 11,791 stool samples (2928 in 2006, 2238 in 2007, 2151 in 2008, 2344 in 2009 and 2130 in 2010) were submitted to the Parasitology section of Department of Microbiology BPKIHS were included in the analysis. Of these, 675 (5.72%) were positive intestinal protozoa and 289 (2.45%) for intestinal helminths. Giardia intestinalis accounted for the most prevalent parasitic infection (3.34%) followed by Entamoeba histolytica/E. dispar (1.96%) and Hookworm (0.97%). A parasitic infection was observed to be highest among 20-50 years of age group and lowest in the less than 5 years group of subjects. Conclusion: Intestinal parasitosis is a common problem. Amoebiasis, giardiasis and the common intestinal helminthes Ascaris lumbricoides, hookworm, and Trichuris trichiura were prevalent in our settings. Asian Journal of Medical Sciences Vol.8(3) 2017 55-59